Preserving Cultural Identity in Intercultural Marriage Between Chinese Indonesian and Javanese Couple During Suharto Era - Jonathan Calvin Candra (Institute of Research and Community Outreach - Petra Christian University, 2022)
The researcher intends to find out how the culture of the husband, which is a Chinese Indonesian can affect or change his wife’s cultural identity as a Javanese amidst the oppression from the Suharto’s government. Cultural theories related to cultural identity will be used to analyse the findings from the respondent. The research will be conducted in semi-structured interview to gain the data from the respondent. The findings suggest that the respondent’s cultural identity as a Javanese develops and shifts. Even though she still has some Javanese culture aspects, the husband indeed influenced the respondent’s identity by his actions and made the respondent embrace some Chinese values like hardworking and discipline.Keywords: intercultural marriage; cultural identity; Chinese Indonesian; Javanese; culture